2015
DOI: 10.1007/s12072-015-9663-8
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular brachytherapy combined with stent placement and TACE for treatment of HCC with main portal vein tumor thrombus

Abstract: These findings suggested that EVBT combined with stent placement and TACE might be a safe and effective palliative treatment option for HCC with main portal vein tumor thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 24 publications
1
70
1
Order By: Relevance
“…Moreover, low dose rate of radiation had been reported to decrease the incidence of metastasis by altering the immunophenotype of the tumor cells [27, 28]. Most importantly, EVBT and sequential 3-DCRT were capable of inhibiting MPVTT [1416, 29]. However, MPVTT treated by these two different types of radiation had never been directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, low dose rate of radiation had been reported to decrease the incidence of metastasis by altering the immunophenotype of the tumor cells [27, 28]. Most importantly, EVBT and sequential 3-DCRT were capable of inhibiting MPVTT [1416, 29]. However, MPVTT treated by these two different types of radiation had never been directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical researches have reported that IRT was suitable for the treatment of pancreatic cancer. [ 28–34 ] Hence, to investigate the effect of CIRT for pancreatic cancer, we adopted human pancreatic cancer (SW1990) cells for all experiments in vitro. First, as sufficient intracellular accumulation of NPs is a prerequisite for an effective treatment, the cellular uptake and intracellular distribution of TiO 2 ‐tyr was visualized via biological TEM (bio‐TEM).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the portal vein pressure is rising with development of PVTT, which increases the risk of esophageal and gastric bleeding and indirectly leads to death [11]. Therefore, opening the occlusion of the portal vein caused by PVTT and reperfusing the portal vein could improve the success of TACE, and this could be achieved using portal vein stenting (PVS) [1214]. PVS combined with TACE has been successfully used in the treatment of HCC with PVTT [6].…”
Section: Introductionmentioning
confidence: 99%